Dural MALT Lymphoma Detected by 11C-Methionine PET/CT. (December 2017) - Annunziata, Salvatore; Cuccaro, Annarosa; Caldarella, Carmelo; Hohaus, Stefan
Abstract : Abstract: A 53-year-old man had a diagnosis of mucosa-associated lymphoid tissue lymphomas of the dura in the left tentorium. The patient underwent whole-body 18 F-FDG PET/CT and 11 C-methionine PET/CT in order to complete the staging of dural mucosa-associated lymphoid tissue lymphoma. 11 C-methionine uptake was detected in multiple meningeal sites, including left tentorium, with no significant FDG uptake in the same regions.